2022
DOI: 10.3389/fimmu.2022.826074
|View full text |Cite
|
Sign up to set email alerts
|

Role of HLA-G in Viral Infections

Abstract: The human leukocyte antigen (HLA)-G is a non-classical HLA class I molecule, which has distinct features to classical HLA-A, -B, -C antigens, such as a low polymorphism, different splice variants, highly restricted, tightly regulated expression and immune modulatory properties. HLA-G expression in tumor cells and virus-infected cells, as well as the release of soluble HLA-G leads to escape from host immune surveillance. Increased knowledge of the link between HLA-G expression, viral infection and disease progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 148 publications
0
9
0
Order By: Relevance
“…There is accumulating evidence that immunosuppressive mechanisms play a major role in promoting viral infection either by suppressing the ability of infected host cells to overcome viral infection or by preventing the elimination of virus-infected cells by immune cells. One common mechanism proposed for viruses to escape immune surveillance is the loss or down-regulation of classical HLA class Ia antigens and neoexpression of non-classical HLA class Ib antigens, such as HLA-E, -F and -G [21] . In COVID-19, it has been suggested that HLA-G may be considered as potent molecules that may suppress immune functions during SARS-CoV-2 infection and thus may enhance virus subversion and allow high rates of replication [22] .…”
Section: Introductionmentioning
confidence: 99%
“…There is accumulating evidence that immunosuppressive mechanisms play a major role in promoting viral infection either by suppressing the ability of infected host cells to overcome viral infection or by preventing the elimination of virus-infected cells by immune cells. One common mechanism proposed for viruses to escape immune surveillance is the loss or down-regulation of classical HLA class Ia antigens and neoexpression of non-classical HLA class Ib antigens, such as HLA-E, -F and -G [21] . In COVID-19, it has been suggested that HLA-G may be considered as potent molecules that may suppress immune functions during SARS-CoV-2 infection and thus may enhance virus subversion and allow high rates of replication [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Although these observations were based on only one patient, they suggest evidence of an association between persistence of SARS-CoV-2, virus-induced inflammation and HLA-G expression. HLA-G induction in host cells infected with SARS-CoV-2 may represent a molecular mechanism for the development of immune evasion as proposed in several human pathogenic viruses [10] . During infection with SARS-CoV-2, the observed decrease in immune-competent cells and the up-regulated expression of pro-inflammatory cytokines is a prominent feature of immunopathology, especially in patients with severe COVID-19 [19] .…”
Section: Discussionmentioning
confidence: 99%
“…HLA-G molecules are expressed in two forms, membrane-bound antigens (HLA-G1, -G2, -G3, and -G4) and soluble proteins (sHLA-G5, -G6 and -G7). Functionally, they are potent immunomodulators and dysregulated expression of HLA-G molecules has been implicated in many pathological conditions including viral infections [10] . In COVID-19, HLA-G molecules are suggested to have immune-regulating effects and up-regulated expression of sHLA-G has been shown in patients with severe disease [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the special immunological condition reported during physiological pregnancy, evidencing the importance of specific immune-regulatory processes, in which a crucial role belongs to the major histocompatibility complex molecules, in humans HLAs (Human Leukocyte Antigens), which are also involved in the response against viral infections [ 47 , 48 ]. The loss or down-regulation of classical HLA class-Ia antigens, as well as the neo-expression of non-classical HLA class-Ib antigens (HLA-E, -F, and -G), is a frequent strategy used by viruses for evading immune surveillance [ 49 , 50 , 51 ].…”
Section: Methodsmentioning
confidence: 99%